The relationship between work-family conflict and burnout amongst call center employees: Optimism and a moderator - Pillay, Jayde (Organisational Psychology, 2021)
This study examined work-family conflict as a predictor of burnout as well as the moderating role that optimism and pessimism may have had on this relationship. Participants were call centre employees from a financial institution in Cape Town (N = 94). Cross-sectional data was collected via electronic self-report questionnaires. Exploratory factor analysis demonstrated the unidimensionality of work-to-family conflict despite the two-dimensional model that was expected. Bivariate regression analysis showed that work-to-family conflict explained a significant proportion of the variance in both dimensions of burnout – emotional exhaustion and cynicism. Contrary to what was expected, the results of the moderation analyses were not significant. Optimism and pessimism did not moderate the relationship between work-to-family conflict and burnout. The results show that work-to-family conflict negatively affects call centre employees' well-being. The results are discussed and implications for management and suggestions for future research are presented.